Dead mammal walking: A month‐long march by a bison (Bison bison) after an ungulate–vehicle collision - Thomas S. Jung; Christopher J. Lewis; Hannah A. Miller; Kazuhisa Kuba; Caeley Thacker (Ecosphere, 2024)
Abstract Globally, ungulate–vehicle collisions (UVCs) are a major human safety concern and may also represent a significant source of mortality for some ungulate populations. However, records of UVC based on counts of roadside carcasses or reports by drivers involved in these incidents are assuredly underestimated because not all ungulates struck die immediately or at the roadside or are reported by drivers or authorities. Here, we provide an observation and analysis of the movements of a GPS‐collared bison (Bison bison) that was involved in a UVC on the Alaska Highway and died in a thick boreal forest 29 days later. During that time, she moved 49.7 km from where she was hit. Her daily movement rate (in kilometers per hour) and daily net displacement (in kilometers per day) were significantly greater in the 29‐day period before she was struck compared with 29 days afterward. This vivid example illustrates that individuals injured in a UVC can die several weeks later and at a considerable distance from where they were initially struck. Moreover, when they eventually die, it may be where their carcass would not be found or associated with a UVC. Bison are the largest land mammal in North America and perhaps more robust to some lower impact UVC than smaller bodied species. Even so, if not for the GPS collar on this bison, we would have never known the fate of this individual, and the carcass likely never found. Taken together, the movements and final resting place of this bison illuminate how estimates of mortality as a result of UVC can be underestimated when the animal does not die immediately and in a location where it can be found. Given our data, we further urge managers to consider roadside counts of animals killed in UVC as a minimum estimate when considering options for mitigation.